Measuring IT Governance Capability at DISKOMINFO Salatiga using COBIT 2019 - Parera, Neonatal March; Tambotoh, Johan Jimmy Charter (Sistemasi: Jurnal Sistem Informasi, 2024)
The rapid development of Information Technology has become a key driver in supporting various sectors and organizational objectives. In the past, information technology was perceived as a support system, but it is now recognized for its significant benefits. Therefore, Information Technology Governance (ITG) is essential to integrate information technology into the organization's strategy. This study aims to measure IT governance capability and provide improvement recommendations using the COBIT 2019 framework to support the vision and mission of DISKOMINFO Salatiga, which is to enhance the quality of public service and achieve good governance The research method employed is qualitative, utilizing the COBIT 2019 framework, and data collection techniques involve observation, interviews, and questionnaires. The results indicate several domains that need enhancement, such as APO12, BAI03, BAI06, BAI07, and BAI10. The identified gap between expected and current capabilities necessitates improvement recommendations, including risk management, system monitoring, structured IT change, project evaluation, and periodic configuration verification. By implementing these recommendations, it is expected that DISKOMINFO Salatiga can achieve the desired IT governance capability, thereby supporting the achievement of Good Governance in line with the organization's vision and mission